Developing learning supplement book of Cell Mitotic Division material for Junior High School students - Intan Putri Syawalinda; Iin Hindun; Diani Fatmawati (Research and Development in Education (RaDEn), 2021)
Cell division is an abstract material for middle school students in which learning resources and supporting learning media are compulsory to use. This research and development aimed at developing learning supplement book of mitotic cell material for IX graders which eases them to identify cell division, particularly in mitotic phase. This study was developed based on ADDIE model which comprised of four stages (i.e. Analysis, Design, Development, Implementation, and Evaluation). The validation test was conducted by teaching and learning material experts. The two stage tests were conducted in small and large trial groups. The qualitative and quantitative data gained were analyzed using percentage. The results showed that the percentage values were 86.2% (very feasible) for teaching material, 99.4% (very feasible) for learning material. The small-scale trial gained 87.8% (very feasible), meanwhile the large-scale test gained 88.3% (very feasible). In conclusion, the mitotic learning supplement book of cell division material for junior high school can be used as teaching material in classroom learning activities.